Dithiol disulphide exchange in redox regulation of chloroplast enzymes in response to evolutionary and structural constraints. (February 2017) - Gütle, Desirée D.; Roret, Thomas; Hecker, Arnaud; Reski, Ralf; Jacquot, Jean-Pierre
Highlights: Disulphide reduction of chloroplast enzymes regulates the rates of photosynthesis. Thioredoxins are key regulators of CO2 fixation. The reducing systems are highly diversified in higher plant eukaryotes. Target enzymes have acquired regulatory sequences at different phylogenetic points. The regulatory sequences are surface-exposed and easily accessible. Abstract: Redox regulation of chloroplast enzymes via disulphide reduction is believed to control the rates of CO2 fixation. The study of the thioredoxin reduction pathways and of various target enzymes lead to the following guidelines: i) Thioredoxin gene content is greatly higher in photosynthetic eukaryotes compared to prokaryotes; ii) Thioredoxin-reducing pathways have expanded in photosynthetic eukaryotes with four different thioredoxin reductases and the possibility to reduce some thioredoxins via glutaredoxins; iii) Some enzymes that were thought to be strictly linked to photosynthesis ferredoxin-thioredoxin reductase, phosphoribulokinase, ribulose-1, 5-bisphosphate carboxylase/oxygenase, sedoheptulose-1, 7-bisphosphatase are present in non-photosynthetic organisms; iv) Photosynthetic eukaryotes contain a genetic patchwork of sequences borrowed from prokaryotes including α–proteobacteria and archaea; v) The introduction of redox regulatory sequences did not occur at the same place for all targets. Some possess critical cysteines in cyanobacteria, for others the transition occurred rather at the green algae level; vi) Generally the regulatory sites of the target enzymes are distally located from the catalytic sites. The cysteine residues are generally not involved in catalysis. Following reduction, molecular movements open the active sites and make catalysis possible; vii) The regulatory sequences are located on surface-accessible loops. At least one instance they can be cut out and serve as signal peptides for inducing plant defence.